Human Governance in Public Transportation Services of Suroboyo Bus for Persons with Disabilities in Surabaya City - Rizky Buana Sari; Bagus Nuari Harmawan (Journal of Government and Politics (JGOP), 2025)
Persons with disabilities in Surabaya remain marginalized in accessing public transportation, often facing discrimination and limited fulfillment of their mobility rights. The City of Surabaya has not yet fully succeeded in building an inclusive public transport system, particularly in the Suroboyo Bus service. This study examines the application of human governance principles in Suroboyo Bus services for persons with disabilities. A qualitative case study was employed, using observation, interviews, and documentation. Informants were selected through purposive and snowball sampling, and data were analyzed using the Miles and Huberman model, including data reduction, display, and conclusion drawing. The findings show that human governance has begun to be applied, though still partial. Social accountability is evident through formal hearings and informal complaint channels, yet integration into decision-making remains limited. Civic education appears in crew training and public campaigns, but implementation lacks continuity. Equality and freedom are promoted through the involvement of disability communities, though challenges persist due to limited empathy among some staff and uneven accessibility. . Participation is encouraged through forums and discussions, although it has not been embedded systematically in policy-making. Adaptive government performance is visible in regulations and accessibility facilities, yet benefits are not fully realized by persons with disabilities. Reliability emerges through crew responsiveness and technology support, but service consistency remains unstable, particularly during peak hours. Inclusive public transportation in Surabaya is progressing but remains incomplete, requiring stronger policies, consistent training, and active involvement of persons with disabilities to achieve equality and justice